037 Updating an Adapted CPG: When Is Enough Enough?. (15th August 2013) - Harstall, C; Moga, C; Scott, A; Taenzer, P; Findlay, T
Abstract : Background: Within 2 years of releasing a low back pain clinical practice guideline (CPG), the Alberta Ambassador Guideline Adaptation Programme was required to update its adapted guideline. No guidance or 'how to' manuals were located. Objectives: To develop a process for updating an adapted guideline. To expedite the process by determining which components can be removed without compromising rigour. Methods: CPGs and systematic reviews published since the release of the CPG were identified and appraised, and discordant and new recommendations were tabulated. The Guideline Development Group (GDG) was surveyed to identify new interventions of interest. Evidence from systematic reviews was included for 'do not know' recommendations and new interventions. Results: The original guideline had 50 recommendations, eight of which were in the 'do not know' category. This expanded to 85 recommendations in the update: 43 unchanged, 32 on GDG-nominated new interventions, and 10 revised. The updated CPG has 33 'do not know' recommendations. One of the original eight 'do not know' recommendations was changed based on new evidence. Discussion: The challenge of maintaining the integrity and high standards of the original guideline meant that the update consumed more time and resources than planned. Clearly, some components of the process can be jettisoned without jeopardising the methodological rigour and comprehensiveness of the final product. Implications: The next update will be streamlined, including only new seed guidelines that meet the quality criteria of the modified AGREE and using systematic reviews to supplement the evidence base when there is discordance among recommendations.